AN ANALYSIS OF STUDENTS’ INHIBITION IN SPEAKING ENGLISH PERFORMANCE - Feri Ferdiyanto; Ainaiyah Shabrina Suciati (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2023)
Speaking is one important skill to be increased and enhanced as tool an effective communication. Speaking English is very challenging for senior high school students. Speaking skill is regarded the most difficult aspect in English language learning. This paper aims to find the inhibition faced by senior high students. This study was conducted by qualitative research to identify the students' speaking performance challenges. The researcher can utilize a variety of methods to gather data for a qualitative study, including field notes, interviews, and record reviews. The findings of the study revealed that the factors that caused inhibition in speaking performance among students were not only related to the students themselves, but also to the teachers as well. To lessen inhibition, the participants also reported that both teachers and students should do different tasks or find ways to lessen inhibition both inside and outside the class during the process of learning English speaking skills.